Body fat, especially visceral fat, is associated with electrocardiographic measures of sympathetic activation. (18th February 2014) - Hillebrand, Stefanie; de Mutsert, Renée; Christen, Tim; Maan, Arie C.; Jukema, J. Wouter; Lamb, Hildo J.; de Roos, Albert; Rosendaal, Frits R.; den Heijer, Martin; Swenne, Cees A.; for the NEO Study Group
<x xml:space="preserve">Abstract</x> Objective Obesity is associated with sympathetic activation, but the role of different fat depots is unclear. The association between body fat, specifically visceral fat, and electrocardiographic measures of sympathetic activation in a population with structurally normal hearts was investigated. Methods In this cross‐sectional baseline analysis of the Netherlands Epidemiology of Obesity study, body fat percentage was assessed with BIA and abdominal subcutaneous (SAT) and visceral adipose tissue (VAT) with magnetic resonance (MR) imaging. Mean heart rate (HR) and five other electrocardiographic measures of sympathetic activation were calculated. We performed multivariate linear regression analyses. Results In 868 participants with a mean age(SD) of 55(6) years, BMI of 26(4) kg/m2, 47% men, body fat was associated with HR and two other measures of sympathetic activation. Per sex‐specific SD total body fat, the difference in HR was 1.9 beats/min (95% CI: 1.0, 2.9; P < 0.001) and per SD waist circumference 2.1 beats/min (95% CI: 1.3, 2.9; P < 0.001). The difference in HR per SD VAT was 2.1 beats/min (95% CI: 1.3, 3.0; P < 0.001). Conclusions Body fat, especially visceral fat, was associated with electrocardiographic measures of sympathetic activation. Our study implies that already before the onset of cardiovascular disease, excess (visceral) body fat is associated with sympathetic activation.